PENGARUH DISIPLIN KERJA, EFIKASI DIRI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN KONAWE KEPULAUAN - Rizka Palando Kamaruddin; Buyung Sarita; Aidin Hudani Awasinombu (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study is to examine and analyze work discipline, self-efficacy, work environment and organizational culture simultaneously on employee performance in BKPSDM of Konawe Islands Regency. The research analysis unit is an employee at the BKPSDM of Konawe Islands Regency. Respondents who were sampled were 39 employees. The data collection technique was carried out by distributing questionnaires. The analytical method used in testing the hypothesis is multiple linear regression analysis with the calculation process using SPSS 21. Qualitative information is used to explore additional information related to the results of hypothesis testing.The results of this study indicate that: Work discipline, self-efficacy, work environment and organizational culture in simultanously has a positive and significant effect on employee performance. Work discipline, self-efficacy, work environment and organizational culture partially significant influence on employee performance in BKPSDM of Konawe Islands Regency. Suggestions for BKPSDM of Konawe Islands Regency can provide good motivation and create better disciplined innovations, maintain friendship with leaders, and provide job training that can support employee performance